Writing Instruction in Large Secondary School EFL Classes: - Jimalee Sowell (Crossings)
English language teachers in countries around the world teach large classes of 35 or more students. While many English language teaching methods since the 18th century have emphasized speaking skills, with globalization has come an increased need for L2 learners in English as a foreign language (EFL) contexts to develop writing skills. However, to date, little research has focused on understanding how writing instruction is carried out in large secondary school EFL classes. The purpose of this qualitative exploratory study was to provide an overview of writing instruction in large secondary school EFL classes. Data was collected through semi-structured interviews with 10 participants with experience as secondary school English language instructors in EFL contexts across continents. Data was analyzed through thematic analysis. Major findings revealed that writing instruction in large EFL secondary school classes is largely dominated by national exams. Additionally, participants indicated a lack of training for teaching writing. However, there was some indication that participants would welcome training. While study participants believed that writing is an important skill, 60 percent were not confident that their secondary school curriculums adequately prepares students for writing beyond secondary school. Implications suggest there is a need to better understand the phenomenon of writing instruction in large secondary school classes through further research. Implications further suggest a need for more training in writing instruction for secondary school teachers working in large EFL contexts.